Formulation of a Concrete Based on Grinded Seashells as Partial Substitution for Sand - Boudjellal, Khaled; Bouabaz, Mohamed; Bensebti, Salah Eddine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper examines the partial substitution of concrete components by grinded sea mussel shells collected from the coastal region of eastern Algeria. The study proposes the recycling of this waste to reduce the excessive and increasing accumulation of these shells to relieve the marine environment. The problem lies in establishing a perfect integration of the aggregates obtained from the grinded shells of sea mussels in the formulation of various types of concrete.
Keywords: mineral aggregates; concrete; cement; sand; grinded seashells; kruszywa mineralne; beton; piasek; muszle zmielone